Spatial Spillover Effects of the Resource Curse: An Empirical Analysis in China - Men, Xiaolu (Frontiers in Environmental Science, 2022)
On the basis of a production function, an economic model consisting of three regions and two departments (resources and conventional departments) is constructed to explore the effect of natural resources on economic development and their spatial correlation. Then, we construct resource abundance and resource dependence indicators. Based on panel data of 30 provinces in China from 2004 to 2020, a spatial Durbin model is used to empirically test the theoretical hypothesis. The results demonstrate that the resource curse exists objectively, and its root lies in resource dependence; increased dependence on resource industries in a region can improve the economic situation of its surrounding regions, and the spatial spillover effect demonstrates obvious nearby features. The marginal measurement result of spatial spillover indicates that the economic effects of local resource dependence on surrounding areas peaks at 250 km. Further categorization discussions confirm that the resource curse in China is mainly the energy curse.